What’s included in Canadians’ rent? - Samuel MacIsaac (Economic and Social Reports)
One in three Canadian households rent their primary residence. Rental costs are often incomparable without accounting for differences across data sources, regions and dwellings (e.g. dwelling type, size, condition). Similarly, a failure to account for differences in terms of non-financial inclusions such as utilities, parking, appliances or air conditioning can undermine the validity of cost comparisons. Using the 2021 Canadian Housing Survey (CHS), this study explores the prevalence of such rental inclusions and their potential impact on rental costs.